ARCAgRP/NPY Neuron Activity Is Required for Acute Exercise-Induced Food Intake in Un-Trained Mice - Bunner, Wyatt; Landry, Taylor; Laing, Brenton Thomas; Li, Peixin; Rao, Zhijian; Yuan, Yuan; Huang, Hu (Frontiers in Physiology, 2020)
While much is known about the role of agouti-regulated peptide/neuropeptide Y (AgRP/NPY) and pro-opiomelanocortin (POMC) neurons to regulate energy homeostasis, little is known about how forced energy expenditure, such as exercise, modulates these neurons and if these neurons are involved in post-exercise feeding behaviors. We utilized multiple mouse models to investigate the effects of acute, moderate-intensity exercise on food intake and neuronal activity in the arcuate nucleus (ARC) of the hypothalamus. NPY-GFP reporter mice were utilized for immunohistochemistry and patch-clamp electrophysiology experiments investigating neuronal activation immediately after acute treadmill exercise. Additionally, ARCAgRP/NPY neuron inhibition was performed using the Designer Receptors Exclusively Activated by Designer Drugs (DREADD) system in AgRP-Cre transgenic mice to investigate the importance of AgRP/NPY neurons in post-exercise feeding behaviors. Our experiments revealed that acute moderate-intensity exercise significantly increased food intake, ARCAgRP/NPY neuron activation, PVNSim1 neuron activation, and while having no effect on ARC POMC neurons. Strikingly, this exercise-induced refeeding was completely abolished when ARCAgRP/NPY neuron activity was inhibited. While acute exercise also increased PVNSim1 neuron activity, inhibition of ARCAgRP/NPY neurons had no effect on PVNSim1 neuronal activation. Overall, our results reveal that ARCAgRP/NPY activation is required for acute exercise-induced food intake in mice, thus providing insight into the critical role of ARCAgRP/NPY neurons in maintaining energy homeostasis in cases of exercise-mediated energy deficit.